Prognostic significance of visceral pleural changes in stage IA lung adenocarcinoma: a retrospective study - Ruan, Yingding; You, Yuhe; Han, Jianwei; Xue, Hongsheng; Cao, Wenjun; Long, Chuan; Sun, Peng; Hu, Yaoyu; Zhao, Zhilong (Frontiers in Oncology, 2025)
BackgroundVisceral pleural changes (VPC) is increasingly detected in early-stage lung adenocarcinoma, but its clinical and prognostic significance is unclear. This retrospective multicenter study aims to evaluate the influence of VPC on OS and DFS in patients with stage IA lung adenocarcinoma.MethodsOverall, 494 patients with stage IA lung adenocarcinoma from two centers were enrolled, including 202 VPC-positive (VPC+) and 292 VPC-negative (VPC-) patients. After 1:1 propensity score matching (PSM), 284 patients (142 per group) were analyzed. The Kaplan–Meier method was used to compare survival between groups, and Cox regression analysis identified independent prognostic factors for OS and DFS.ResultsKaplan–Meier analysis showed no significant OS difference between VPC+ and VPC- group (HR 0.67, 95% CI 0.31–1.47, P = 0.320). However, DFS was significantly better in VPC+ patients compared to VPC- patients (HR 0.51, 95% CI 0.27–0.94, P = 0.028). Specifically, 5-year OS was 96.5% in VPC+ vs. 95.8% in VPC- (P = 0.845), and 5-year DFS was 95.8% in VPC+ vs. 92.3% in VPC-(P = 0.259), with no significant differences. Median OS was 76.0 months before PSM and 76.0 months after PSM. For DFS, median time was 76.0 months before PSM and 76.0 months after PSM. Cox regression identified operative time as an independent OS prognostic factor (HR 1.01, 95% CI 1.00–1.11, P = 0.039), while VPC- (HR 0.40, 95% CI 0.19–0.83, P = 0.015) and pathological stage IA3 (HR 3.12, 95% CI 1.08–9.00, P = 0.035) were independent DFS prognostic factors.ConclusionIn patients with stage IA lung adenocarcinoma, VPC- is associated with worse DFS compared to VPC+, while no significant difference in OS was observed. Pathological stage were significant prognostic factors for DFS.